Exploring the lived experiences of parents raising a child diagnosed with Duchenne Muscular Dystrophy (DMD) in South Africa : challenges and coping strategies - Eskell-Blokland, Linda (University of Pretoria, 2020)
Mini Dissertation (MA (Counselling Psychology))--University of Pretoria, 2020.